The Reasons of Israel's Agresivity on Palestinians in Gaza Strip: 2008 -2014 - Evany Sofia Prameswari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In the conflict between Israel and Palestine, Israel had been overreacted by carrying out intensive military attacks that caused more Palestinian civilian casualties than Israelis. During the period 2008-2014 Israel carried out several aggressive military attacks which resulted in an increase in Palestinian civilian casualties, especially in the Gaza Strip. Using a constructivist perspective, this thesis will explain the reasons for Israel’s aggressiveness towards Palestine, especially in the Gaza Strip, in the period 2008-2014. The main idea is identity. Israel’s collective identity was formed because of the bad historical experience of the Jewish people that grew up amid conflictual conditions. This formed a siege mentality and hatred in the lives of the Jews so that they assumed that groups outside them had evil intentions. It is important to understand how Israel's perception of self-image to trace the construction of thought of the leaders over that time span. Meanwhile, Palestinian identity changes from time to time due to certain social and historical factors. This difference causes both of them not to share the same identity (shared identity), which also influences Israel’s perception that Palestine is a threat. The inherent aggressive mentality, lack of shared identity, Israel’s perception of self-image and perceived threat from Israel are the causes of Israel’s aggressiveness towards Palestinians, especially in the Gaza Strip.